ORGANIZATIONAL ENSURING THE DEVELOPMENT OF LABOR POTENTIAL OF BUSINESS STRUCTURES AS A COMPONENT OF STRATEGIC MANAGEMENT - Савченко, Віра; Кононенко, Леся; Карнаушенко, А.С. (Modern engineering and innovative technologies, 2023)
The article is devoted to the problems of assessment and formation of labor potential. The problems and prospects of the formation of labor potential under the condition of applying permanent education are studied. The current problems of ensuring the goa